THE EFFECTIVENESS OF SMALL GROUP DISCUSSION ON IMPROVING STUDENTS' SPEAKING ABILITY IN DESCRIPTIVE TEXT - Dini Irawati,; Aulia Indira Choirunnisa,; Siti Hadijah,; Amalia Nuraini, (Jurnal Cakrawala Ilmiah, 2024)
Speaking is a crucial aspect of language acquisition as it allows students to demonstrate their competence in the language they are learning. However, various obstacles can impact students' speaking abilities, including a lack of confidence, a limitation of vocabulary and grammar, and ineffective teaching methods. The objectives of this research were to investigate whether the effectiveness of Small Group Discussion improves speaking ability in descriptive text at the seventh grade of SMPN 14 Samarinda in the academic year 2023/2024 and to determine whether Small Group Discussion helps students enhance their speaking ability in descriptive text in the seventh grade at S MPN 14 Samarinda in the academic year 2023/2024. This research employed a quantitative approach with a quasi-experimental design. The sample consisted of seventh-grade students from SMPN 14 Samarinda, specifically classes 7A and 7C. Data were collected through observation, documentation, and speaking tests to describe the progress of the action. The average score and class percentage were used as a representation of students' speaking improvement. The findings of this research was there are increase of 0.35% in the experimental class (30 to 40.5) and an increase of 0.15% in the control class (26.06 to 29.94) which means that Small Group Discussion has a better and significant improvement compared to conventional learning. According to Mann-whitney test, Asymp , significance value (2-tailed) was <0.001, which is less than α (0.005). It could be concluded that Ha accepted and Ho refused. It means small group discussion had significant effect on students speaking skill in the descriptive text at seventh grade students of SMPN 14 Samarinda